Stroke Related Anxiety and Secondary Stroke Prevention Practices among Stroke Survivors - Sah, Chanda; Shah, Sanjeev; Neupane, Gita; Shrestha, Pragya; Ghimire, Sulochana (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTIONStroke is a leading cause of death and permanent disability worldwide. A secondary stroke, also known as a recurrent stroke, is one which occurs 24 hours or more after a primary stroke. The objective of this study was to find out the stroke related anxiety, knowledge related to the risk factors of stroke and practices among stroke survivors to prevent secondary stroke.  MATERIAL AND METHODSDescriptive cross-sectional study was conducted to find out stroke related anxiety and secondary stroke prevention practices among 76 purposively selected stroke survivors. Semi- structured interview schedule and Hospital Anxiety and Depression Scale (HADS) were used to collect data. Descriptive statistics (frequency and percentage) were used with SPSS version 20.0 for data analysis.RESULTSThe findings of the study showed that out of 76 stroke survivors, 13.16% had borderline anxiety and 11.84 % were abnormal cases of anxiety. Knowledge on risk factors of secondary stroke as old age (94.74%), physical inactivity (55.26%), smoking (60.53%), excessive alcohol consumption (63.16%) and hypertension (92.11%).  Poor practices were found regarding secondary stroke prevention such as monitoring blood pressure regularly (26.53%), regular exercise (40.79%), nearly half had not reduced alcohol intake (44.19%) and had not quit smoking (48.15%).CONCLUSIONFindings of the study showed presence of stroke related anxiety among stroke survivors and poor secondary stroke prevention practices. These data will be helpful for concerned authority to focus on management of post stroke anxiety. It is recommended to concerned authority to conduct awareness program on secondary stroke prevention practices.